Optimizing the Role of Youth Organization Through the Implementation of Ministerial Regulation and the Perspective of Fiqh Siyasah Tanfidziyyah - Safitri, Ani Ayu; Firdawaty, Linda; Santoso, Rudi (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The implementation of the Ministerial Regulation plays a crucial role in enhancing the effectiveness of the Karang Taruna organization, in accordance with the Regulation of the Minister of Social Affairs Number 25 of 2019. This study aims to analyze the role of youth organization or Karang Taruna in Cempaka Barat Village, particularly in relation to Article 6 of Permensos 25/2019, from the perspective of Fiqh Siyasah Tanfidziyyah. The research employs a field study approach using a case study of the local Karang Taruna organization. The findings indicate that while Karang Taruna has made efforts to optimize its role, it continues to face challenges, including limited funding and the absence of many members due to work or study commitments outside the region. The principles of Fiqh Siyasah Tanfidziyyah have been found to be highly relevant in improving organizational effectiveness. This study underscores the importance of adaptive policies to support the role of Karang Taruna in promoting social development within village communities.